Factores psicosociales y su influencia en el consumo de cocaína en una persona de 17 años de edad en el cantón Caluma - Gavilanes Garcia, Jean Paoli (2021)
The present case study was carried out with the objective of identifying with psychological techniques and Cognitive Behavioral therapy if psychosocial factors influence cocaine use in a 17-year-old person in the canton of caluma. In this way, the qualitative methodology used in this work is aimed at the scientific investigation of variables such as: Psychosocial factors and cocaine consumption, which are exposed in this case study, and the use of different techniques was required. Cognitive Behavioral Therapy, which allowed the proposed objective to be optimally fulfilled, to later provide the corresponding therapy to the patient through a therapeutic plan which includes a cognitive restructuring procedure aimed at modifying those thoughts that the patient presented during the intervention psychological, all this in order for the patient to overcome his problem and improve his quality of life both personal and social.